Relatório de estágio curricular supervisionado em medicina veterinária – áreas de clínica médica e cirúrgica de pequenos animais e patologia veterinária - Mendes, Vanessa Pereira (2018)
This report describes the activities developed and monitored during the Internship Supervised Curriculum in Veterinary Medicine (ECSMV), under the guidance of Profa. Dr. Maria Elisa Trost, covering the areas of Medical Clinic, and Small Surgical Animals and Veterinary Pathology. First developed at Clínica Veterinária - CVet, in the city of Uruguaiana-RS, in the area of Small Animal Medical and Surgical Clinic, in the period from July 30 to August 31, 2018, making a total of 200 hours. In the first stage the academic participated in activities such as veterinary consultations on small animals, surgeries and care of hospitalized animals, under the supervision of veterinarian Mariana da Silva Fernandes. During this period, 286 procedures were followed, with surgical care the most prevalent (36% of the total) followed by clinical care (26%), immunoprophylaxis and vermin (20%), and material collection (18%). Were described detail the cases of a dog undergoing necropsy and diagnosed with canine parvovirus and a cat undergoing necropsy exam diagnosed with pleuritis bacterial. The second part of the internship took place at the Veterinary Pathology Laboratory - LPV-Unipampa, in the city of Uruguaiana-RS, under the supervision of Professor Dr. Bruno Leite from Angels. This stage of the internship took place from September 3 to September 19 October 2018, making a total of 256 hours. The academic participated in activities such as necropsies, histopathological processing, slide reading and preparation of reports with the observed changes. During this period, 29 autopsies and 58 histopathological exams in different species, mostly in canines. Were described in detail the cases of two sheep with chronic copper poisoning and one aspiration bronchopneumonia in a rodent, both necropsied and evaluated histologically in the laboratory.